The effect of bile salt diet supplementation on genes related to fat metabolism in yellow-feathered broilers - Zhenming Zhang; Baoan Ding; Hailian He; Jingge Wang; Xiongjie Liu; Jiahui Guo; Pengxiang Li; Stephen R. Madigosky (Veterinary World, 2022)
Background and Aim: As a new feed additive, bile acid (BA) can promote the absorption and transport of lipids and fat-soluble vitamins. In recent years, BAs have been widely used in animal feed to promote fat absorption. Therefore, this study aimed to investigate the effect of bile salt supplementation in the diet of yellow-feathered broilers on messenger RNA (mRNA) expression of sterol regulatory element-binding protein 1 (SREBF1), fatty acid synthase (FAS), acetyl-coenzyme A carboxylase (ACC), and fatty acid transport protein 4 (FATP4).